2009
DOI: 10.1371/journal.pone.0004317
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Pathology of Pediatric Cerebral Malaria in Malawi

Abstract: IntroductionThe causes of coma and death in cerebral malaria remain unknown. Malarial retinopathy has been identified as an important clinical sign in the diagnosis and prognosis of cerebral malaria. As part of a larger autopsy study to determine causes of death in children with coma presenting to hospital in Blantyre, Malawi, who were fully evaluated clinically prior to death, we examined the histopathology of eyes of patients who died and underwent autopsy.Methodology/Principal FindingsChildren with coma wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
111
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 32 publications
2
111
3
1
Order By: Relevance
“…50 Furthermore, IHC enabled us to obtain detailed information about the perivascular expression pattern and to pinpoint neuronal and perivascular hypoxia due to cerebral hypoperfusion. Considered together with the bulk of data on hypoperfusion in murine and human CM, 15,17,20,23,25,28,76 this new approach seems appropriate for further mechanistic research. The results overall suggest that cerebral hypoperfusion leads to tissue hypoxia in murine CM and that this is likely a key event in development of acute cerebral disease.…”
Section: Hypoxia and Cerebralmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Furthermore, IHC enabled us to obtain detailed information about the perivascular expression pattern and to pinpoint neuronal and perivascular hypoxia due to cerebral hypoperfusion. Considered together with the bulk of data on hypoperfusion in murine and human CM, 15,17,20,23,25,28,76 this new approach seems appropriate for further mechanistic research. The results overall suggest that cerebral hypoperfusion leads to tissue hypoxia in murine CM and that this is likely a key event in development of acute cerebral disease.…”
Section: Hypoxia and Cerebralmentioning
confidence: 99%
“…Noninvasive imaging of retinal and rectal vessels in patients with CM clearly demonstrates hypoperfusion and occlusion of the microcirculation, [15][16][17][18][19][20][21] which is reflected by a clear association with a poor clinical outcome. 16,[21][22][23] Murine models of CM have important similarities to CM in humans 2,24 including increased intracranial pressure and a significant decrease in cerebral blood flow, which progressively deteriorates as the clinical condition becomes aggravated.…”
mentioning
confidence: 99%
“…2 In this respect, it is interesting to note that Loa-related SAEs and severe malaria share many clinical features, including fever, impaired consciousness, and white-centered retinal hemorrhages. 6 In addition, Plasmodium infection has been observed in a number of individuals who developed post-ivermectin SAEs. 7 Thus, Plasmodium infection has been considered as a potential cofactor facilitating the development of SAEs.…”
mentioning
confidence: 99%
“…The diagnostic importance of the visual system in patients with CM has recently been highlighted, 22 and the optic nerve has been proposed as an important diagnostic marker for patient classification, risk assessment, and monitoring of CM. 23 White and colleagues 24 specifically showed that although the detection of hemorrhages per se in the retina is not a clear predictor of outcome in patients with CM, the number and severity of hemorrhages correlate with morbidity. Ma and colleagues, 25 who were the first to examine the pathologic abnormalities of the optic nerves in murine CM, demonstrated loss of axonal viability in this disease in any central nervous system tissue, which corroborated with reports of demyelination in human CM.…”
Section: Discussionmentioning
confidence: 99%